KEBERHASILAN BELAJAR SISWA SMA DITELAAH DARI POLA ASUH ORANG TUA: (Studi Deskriptif Analitik Terhadap Siswa SMA Negeri 4 DKI Jakarta) - Nurhasanah (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2016)
their learning and success, as well as the contribution of parenting to the success of student learning. The data used in this study were obtained through questionnaires and documentation (books leger). The study population was all students of SMAN 4 Jakarta. Through statistical calculations obtained a sample of 151 students. Penerikan sample is done through proportional stratified random sampling technique. To illustrate the tendency of patterns of care and success in learning to use comparative analysis between the mean score of actual with the ideal score. Fatherly illustrates the contribution made by the partial correlation analysis. Based on the analysis of the results of the study, found that: a). parenting used parents tend to be coaching you. Offset by loose love parenting. While the pattern of care show of power was perceived as being neutral students. b). The success of student learning tends to be in the medium category. c). patterns of care that contribute to positive and tangible to the success of student learning is the pattern of care bina love (15.41%). While the pattern of care and show off the power of love are less likely to contribute significantly to the success of student learning.